The effect of Al(NO3)3 concentration on the formation of AuNPs using low temperature hydrothermal reaction for memory application - Ng, S.A.; K.A. Razak,; Cheong, K.Y.; Aw, K.C. (Penerbit Universiti Kebangsaan Malaysia, 2016)
Distribution of gold nanoparticles (AuNPs) on a substrate becomes crucial in nanotechnology applications. This work describes a route to fabricate AuNPs directly on silicon substrates by using an aluminum template in hydrothermal reaction at 80°C for 1 h. The effect of aluminum nitrate (Al(NO3)3) concentration in the hydrothermal bath was investigated. The properties of AuNPs were studied using field-emission scanning electron microscope (FESEM), x-ray diffractometer (XRD) and semiconductor characterization system (SCS). Two distinct sizes of AuNPs were observed by FESEM. XRD analysis proved the formation of AuNPs directly on the substrate. AuNPs were embedded between polymethylsilsesquioxane (PMSSQ) in order to investigate their effect on memory properties. The sample grown in 0.1 M Al(NO3)3 exhibited the largest hysteresis window (2.6 V) and the lowest Vth (2.2 V) to turn ‘ON’ the memory device. This indicated that good distribution of FCC structure AuNPs with 80±4 nm and 42±7 nm of large and small particles produced better charge storage capability. Charge transport mechanisms of AuNPs embedded in PMSSQ were explained in details whereby electrons from Si are transported across the barrier by thermionic effects via field-assisted lowering at the Si-PMSSQ interface with the combination of the Schottky and Poole Frenkel emission effect in Region 1. Trapped charge limited current (TCLC) and space charge limited current (SCLC) transport mechanism occurred in Region 2 and Region 3.